Results 1 to 3 of 3

Math Help - radius of convergence

  1. #1
    Newbie
    Joined
    Jul 2008
    Posts
    2

    radius of convergence

    Hi please could you assist me: questions posted below:


    Assuming the function f is holomorphic in the disk D(0,1) = \{ z \in \mathbb{C}:|z| < 1\}, prove that g(z) = \overline {f(\overline z )} is also holomorphic in D(0,1) and find its derivative?????



    Find the radii of convergence of the following series stating which result is being used.
    (a) \sum\limits_{k = 0}^\infty  {k^{113} 2^{ - k} (z - 1)^k }

    (b) \sum\limits_{n = 2}^\infty  {n!(z - e)^{3n} }

    (c) \sum\limits_{k = 0}^\infty  {\frac{{z^k }}{{(k!)^2 }}}


    (A)
    Using Ratio Test:

    \mathop {\lim }\limits_{k \to \infty } \left| {\frac{{a_{k + 1} }}<br />
{{a_k }}} \right| = \mathop {\lim }\limits_{k \to \infty } \left| {\frac{{(k + 1)^{113} 2^{ - (k + 1)} (z - 1)^{k + 1} }}{{k^{113} 2^{ - k} (z - 1)^k }}} \right| =

    <br />
\mathop {\lim }\limits_{k \to \infty } \left| {\frac{{(k + 1)^{113} 2^{ - k - 1} (z - 1)^{k + 1} }}{{k^{113} 2^{ - k} (z - 1)^k }}} \right| = \mathop {\lim }\limits_{k \to \infty } \left| {\frac{{(k + 1)^{113} 2^{ - 1} (z - 1)}}{{k^{113} }}} \right|

    = \frac{{(\infty  + 1)^{113} 2^{ - 1} (z - 1)}}{{\infty ^{113} }} = \frac{{(z - 1)}}<br />
{2} < 1

    So is rad. of convergence (z-1)/2 and converging since it is less than 1??



    (B)

    Using Ratio Test:

    \mathop {\lim }\limits_{n \to \infty } \left| {\frac{{a_{n + 1} }}<br />
{{a_n }}} \right| = \mathop {\lim }\limits_{n \to \infty } \left| {\frac{{(n + 1)!(z - e)^{3(n + 1)} }}{{n!(z - e)^{3n} }}} \right| = \mathop {\lim }\limits_{n \to \infty } \left| {(n + 1)(z - e)^3 } \right|

    = (\infty  + 1)(z - e)^3  = \infty

    Hence, is ROC infinity and diverging since it is greater than 1?

    (C)
    Using Ratio Test:

    \mathop {\lim }\limits_{k \to \infty } \left| {\frac{{a_{k + 1} }}<br />
{{a_k }}} \right| = \mathop {\lim }\limits_{k \to \infty } \left| {\frac{{z^{k + 1} }}{{((k + 1)!)^2 }} \times \frac{{(k!)^2 }}<br />
{{z^k }}} \right| = \mathop {\lim }\limits_{k \to \infty } \left| {\frac{{z^{k + 1} }}{{z^k }} \times \frac{{(k!)^2 }}<br />
{{((k + 1)!)^2 }}} \right|

    = \mathop {\lim }\limits_{k \to \infty } \left| {z \times \frac{{(k!)^2 }}{{((k + 1)!)^2 }}} \right| = \mathop {\lim }\limits_{k \to \infty } \left| {\sqrt z \frac{{k!}}{{k + 1!}}} \right|

     = \mathop {\lim }\limits_{k \to \infty } \left| {\frac{{\sqrt z }}<br />
{{k + 1}}} \right| = \frac{{\sqrt z }}{{\infty  + 1}} = 0

    So is ROC 0 and converging since it is less than 1?
    Follow Math Help Forum on Facebook and Google+

  2. #2
    MHF Contributor

    Joined
    May 2008
    Posts
    2,295
    Thanks
    7
    Quote Originally Posted by rinatoc View Post

    Assuming the function f is holomorphic in the disk D(0,1) = \{ z \in \mathbb{C}:|z| < 1\}, prove that g(z) = \overline {f(\overline z )} is also holomorphic in D(0,1) and find its derivative?????

    using complex conjugate properties and this fact that z \rightarrow a iff \overline{z} \rightarrow \overline{a}, we get:

    \lim_{z\to a} \frac{g(z)-g(a)}{z-a}=\lim_{z\to a} \frac{\overline{f(\overline{z})} - \overline{f(\overline{a})}}{z-a}=\lim_{\overline{z}\to \overline{a}} \overline{\left(\frac{f(\overline{z})-f(\overline{a})}{\overline{z}-\overline{a}} \right)}

    =\overline{\left(\lim_{\overline{z}\to \overline{a}} \frac{f(\overline{z})-f(\overline{a})}{\overline{z}-\overline{a}} \right)} \ \ \ \ \ \text{since the map} \ \ z \rightarrow \overline{z} \ \ \text{is continuous}

    =\overline{f'(\overline{a})}. thus g is holomorphic too and g'(z)=\overline{f'(\overline{z})}. \ \ \ \square


    Find the radii of convergence of the following series stating which result is being used.
    (a) \sum\limits_{k = 0}^\infty {k^{113} 2^{ - k} (z - 1)^k }

    (b) \sum\limits_{n = 2}^\infty {n!(z - e)^{3n} }

    (c) \sum\limits_{k = 0}^\infty {\frac{{z^k }}{{(k!)^2 }}}


    (A)
    Using Ratio Test:

    \mathop {\lim }\limits_{k \to \infty } \left| {\frac{{a_{k + 1} }}<br />
{{a_k }}} \right| = \mathop {\lim }\limits_{k \to \infty } \left| {\frac{{(k + 1)^{113} 2^{ - (k + 1)} (z - 1)^{k + 1} }}{{k^{113} 2^{ - k} (z - 1)^k }}} \right| =

    <br />
\mathop {\lim }\limits_{k \to \infty } \left| {\frac{{(k + 1)^{113} 2^{ - k - 1} (z - 1)^{k + 1} }}{{k^{113} 2^{ - k} (z - 1)^k }}} \right| = \mathop {\lim }\limits_{k \to \infty } \left| {\frac{{(k + 1)^{113} 2^{ - 1} (z - 1)}}{{k^{113} }}} \right|

    = \frac{{(\infty + 1)^{113} 2^{ - 1} (z - 1)}}{{\infty ^{113} }} = \frac{{(z - 1)}}<br />
{2} < 1

    So is rad. of convergence (z-1)/2 and converging since it is less than 1??[/tex]

    you should say that \lim_{k\to\infty} \frac{(k+1)^{113}}{k^{113}} = 1, rather than putting k=\infty!!!

    so you got |z-1| < 2, which means that the radius of convergence is 2.


    (B)

    Using Ratio Test:

    \mathop {\lim }\limits_{n \to \infty } \left| {\frac{{a_{n + 1} }}<br />
{{a_n }}} \right| = \mathop {\lim }\limits_{n \to \infty } \left| {\frac{{(n + 1)!(z - e)^{3(n + 1)} }}{{n!(z - e)^{3n} }}} \right| = \mathop {\lim }\limits_{n \to \infty } \left| {(n + 1)(z - e)^3 } \right|

    = (\infty + 1)(z - e)^3 = \infty

    Hence, is ROC infinity and diverging since it is greater than 1?

    so the series is divergent for all values of z except for z=e. thus the radius of convergence is 0.


    (C)
    Using Ratio Test:

    \mathop {\lim }\limits_{k \to \infty } \left| {\frac{{a_{k + 1} }}<br />
{{a_k }}} \right| = \mathop {\lim }\limits_{k \to \infty } \left| {\frac{{z^{k + 1} }}{{((k + 1)!)^2 }} \times \frac{{(k!)^2 }}<br />
{{z^k }}} \right| = \mathop {\lim }\limits_{k \to \infty } \left| {\frac{{z^{k + 1} }}{{z^k }} \times \frac{{(k!)^2 }}<br />
{{((k + 1)!)^2 }}} \right|

    = \mathop {\lim }\limits_{k \to \infty } \left| {z \times \frac{{(k!)^2 }}{{((k + 1)!)^2 }}} \right| = \mathop {\lim }\limits_{k \to \infty } \left| {\sqrt z \frac{{k!}}{{k + 1!}}} \right|

     = \mathop {\lim }\limits_{k \to \infty } \left| {\frac{{\sqrt z }}<br />
{{k + 1}}} \right| = \frac{{\sqrt z }}{{\infty + 1}} = 0

    So is ROC 0 and converging since it is less than 1?

    where did \sqrt{z} come from??! since (k+1)!=(k+1)k!, you'll get:

    \lim_{k\to\infty} \left|\frac{a_{k+1}}{a_k} \right| = \lim_{k\to\infty} \frac{|z|}{(k+1)^2}=0 < 1, \ \ \forall z. so the radius of convergence is \infty.
    Last edited by NonCommAlg; July 8th 2008 at 05:57 PM.
    Follow Math Help Forum on Facebook and Google+

  3. #3
    Junior Member
    Joined
    Jul 2008
    Posts
    29
    Quote Originally Posted by NonCommAlg View Post
    so the series is divergent for all values of z except for z=e. thus the radius of convergence is 0.
    i understand your method here, thanks for that. but why is it 0.
    is there a general rule saying that the ROC is 0 if the function is divergent everywhere except for one point?



    Quote Originally Posted by NonCommAlg View Post
    where did \sqrt{z} come from??! since (k+1)!=(k+1)k!, you'll get:

    \lim_{k\to\infty} \left|\frac{a_{k+1}}{a_k} \right| = \lim_{k\to\infty} \frac{|z|}{(k+1)^2}=0 < 1, \ \ \forall z. so the radius of convergence is \infty.
    lol i was trying to square root the z so that it would be easier to work with the k's but your method is more appropriate.
    as before though, why is the ROC infinity. is there a general rule saying that if you get the value as 0 then the ROC is infinity?
    how did you conclude these answers?

    thanx very much for the help btw, very much appreciated!!!
    Last edited by mathfied; July 9th 2008 at 12:02 PM.
    Follow Math Help Forum on Facebook and Google+

Similar Math Help Forum Discussions

  1. Replies: 7
    Last Post: March 27th 2011, 08:42 PM
  2. Replies: 1
    Last Post: May 13th 2010, 02:20 PM
  3. Replies: 2
    Last Post: May 1st 2010, 10:22 PM
  4. Replies: 1
    Last Post: November 13th 2009, 07:42 AM
  5. series convergence and radius of convergence
    Posted in the Calculus Forum
    Replies: 1
    Last Post: November 15th 2008, 09:07 AM

Search Tags


/mathhelpforum @mathhelpforum